An Injectable Cytokine Trap for Local Treatment of Autoimmune Disease. (February 2020) - Zamecnik, Colin R.; Levy, Elizabeth S.; Lowe, Margaret M.; Zirak, Bahar; Rosenblum, Michael D.; Desai, Tejal A.
Abstract: Systemic cytokine therapy is limited by toxicity due to activation of unwanted immune cells in off-target tissues. Injectable nanomaterials that interact with the immune system have potential to offer improved pharmacokinetics and cell specificity compared to systemic cytokine therapy by instead capturing and potentiating endogenous cytokine. Here we demonstrate the use of high aspect ratio polycaprolactone nanowires conjugated to cytokine-binding antibodies that assemble into porous matrices when injected into the subcutaneous space. Nanowires are well tolerated in vivo over several weeks, incite minimal foreign body response and resist clearance. Nanowires conjugated with JES6-1, an anti-interleukin-2 (IL-2) antibody, were designed to capture endogenous IL-2 and selectively activate tissue resident regulatory T cells (Tregs). Together these nanowire-antibody matrices were capable of sequestering endogenous IL-2 in the skin and were successful in rebalancing local immune compartments to a more suppressive, Treg-mediated phenotype in both wild type and transgenic murine autoimmune disease models. Graphical abstract: Image 1 Highlights: Polymeric nanowires conjugated to anti-cytokine antibodies can sequester endogenous cytokines in vivo . Nanowires are stable in vivo and do not induce foreign body response until degradation 6 weeks post-injection into the skin. Immunomodulation is restricted to the skin by passive accumulation of target cytokine without need for dosing systemically. Immunosuppressive antibody-conjugated nanowires restrict pleiotropism of cytokine and activate only regulatory T cells. When injected into animals with skin-based autoimmune disease, nanowires suppress immune response and mitigate lesions.